Task support in an office system - 264793 Croft, W. Bruce; Lefkowitz, Lawrence S.
A major goal of an office system is to support tasks that are central to office functions. Some office tasks are readily implemented with generic officetools, such as calendars, forms packages, and mail. Many tasks, however, involve complex sequences of actions which do not all correspond to tool invocations but, instead, rely on the problem-solving abilities of office workers. In this paper we describe a system (POISE) than can be used to both automate routine tasks and provide assistance in more complex situations. The type of assistance provided can range from maintaining a record of the tasks corrently being executed to suggesting possible next steps and answering naturallanguage queries about the tasks. The POISE system uses both a procedure-based and a goal-based representation of the tasks to achieve efficiency and flexibility. The mechanisms used by POISE are described with example procedures from a university offfice. Categories and Subject Descriptors: H.4.1 (Information Systems Applications): Office Automation;H.4.2(Information Systems Applications): Types of Systems-decision support;I.2.1 (Artificial Intelligence): Applications and Expert Systems-office automation;I.2.4 (Artificial Intelligence): Knowledge Representation Formalisms and Methods-representations (procedural and rule-based). General terms: Design, Management. Additional keywords and Phrases: Natural language, problem-solving, tools.